A case of biodiversity overestimation in the Balkan Belgrandiella A. J. Wagner, 1927 (Caenogastropoda: Hydrobiidae): molecular divergence not paralleled by high morphological variation. Issue 5 (9th February 2018) - Osikowski, Artur; Hofman, Sebastian; Rysiewska, Aleksandra; Sket, Boris; Prevorčnik, Simona; Falniowski, Andrzej
ABSTRACT: Belgrandiella A. J. Wagner, 1927 is a genus comprising minute snails with conic or turriform shells that are facultative stygobionts, inhabiting subterranean waters and springs. Few specimens or even empty shells of this taxon can be found, so the taxonomy is based mostly on the shell morphology and geographic distribution. Anatomy is known for a few taxa, and its usefulness is restricted. This, coupled with a popular idea that isolation is the first factor shaping divergence and speciation of the spring/cave fauna, resulted in dozens of nominal species of Belgrandiella, known from shells at a given locality. Herein we present shells, anatomy and four molecular markers (nuclear H3, 18S and 28S and mitochondrial cytochrome oxidase subunit I) in Belgrandiella from 16 localities in Slovenia, northern Croatia, and Bosnia and Herzegovina. Five sites are type localities of Boleana umbilicata, Belgrandiella kusceri, Belgrandiella krupensis, Belgrandiella zermanica and Belgrandiella robusta, respectively. Considering the shell and geographic distribution, we have determined B . cf. robusta Belgrandiella cf. croatica, Belgrandiella cf. fontinalis, Belgrandiella cf. kuesteri, Belgrandiella cf. pageti and Belgrandiella cf. koprivnensis The shells of all, as well as penes and female reproductive organs of two putative, species have been illustrated. Molecular analysis indicates four distinct clades, most probably of species rank for B. kusceri, B . cf. kuesteri, B . cf. fontinalis and B . cf. koprivnensis . Four nominal species ( B. krupensis, B. robusta, B. umbilicata and B. zermanica ) and one genus ( Boleana ) must be synonymised with Belgrandiella kusceri, and there are no more than four valid, biological species in the studied Belgrandiella . The molecular divergence is completely unmirrored by high morphological variability. Hence the level of endemism is markedly overestimated in these snails.